2019
DOI: 10.1149/2.1211912jes
|View full text |Cite
|
Sign up to set email alerts
|

Egg-Shell Like Hollow Alumina Sphere Modified Electrode for Enhanced Electrochemical Determination of Metronidazole

Abstract: An egg shell like alumina hollow sphere was prepared using hydrothermally synthesised carbon sphere as hard template. Extensive studies have been carried out to characterize the alumina hollow sphere using different experimental techniques, such as FE-SEM, XRD, TGA, BET and electrochemical impedance spectroscopy (EIS). The electrochemical behavior of metronidazole (MNZ) drug was investigated using Al 2 O 3 hollow shell modified glassy carbon electrode (GCE) and a well-defined irreversible reduction peak was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The electrochemical methods are considered as an alternate instrumental method to overcome the above‐said obstacles. The low‐cost electrochemical techniques are appropriate for the quantitative determination of analytes due to their high sensitivity and lower detection limit 43–46 . In the present work, we developed a methodology based on sulfur‐doped graphitic carbon nitride as an electrode modifier to facilitate the electrochemical reaction, and thereby we can achieve higher sensitivity than the previously reported methods.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The electrochemical methods are considered as an alternate instrumental method to overcome the above‐said obstacles. The low‐cost electrochemical techniques are appropriate for the quantitative determination of analytes due to their high sensitivity and lower detection limit 43–46 . In the present work, we developed a methodology based on sulfur‐doped graphitic carbon nitride as an electrode modifier to facilitate the electrochemical reaction, and thereby we can achieve higher sensitivity than the previously reported methods.…”
Section: Introductionmentioning
confidence: 98%
“…The low-cost electrochemical techniques are appropriate for the quantitative determination of analytes due to their high sensitivity and lower detection limit. [43][44][45][46] In the present work, we developed a methodology based on sulfur-doped graphitic carbon nitride as an electrode modifier to facilitate the electrochemical reaction, and thereby we can achieve higher sensitivity than the previously reported methods. Herein for the first time, we employed high energy ball milling method to prepare S-doped graphitic carbon nitride and then characterized it with various analytical methods to understand structural characteristics, electronic properties, and crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…31 Recently, Kalaiyarasi and Pandian prepared an Al 2 O 3 hollow sphere based on the carbon sphere as a hard template and then successfully exploited it for electrochemical determination of MNZ in tablets and urine samples. 32 Jiaguo et al, have been reported as template free the hollow spheres in high yields by a facial hydrothermal reaction by using urea and potassium aluminium sulphate reaction mixtures. 33 Similar we can prepare various hollow spheres and metal oxides using the carbon sphere as a hard template for different applications.…”
mentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27] Recently the reported articles highlighted about electrochemical biosensing of living cell's cofactors, 28 organophosphate pesticides, 29 phenolic compounds, 30 and monitoring of microbial cell viability 31 using cost-effective 32 aluminum modifiers. [33][34][35][36][37] In this article, a novel method for the sensitive and selective detection of OMZ by direct reduction method was reported. Al 2 O 3 NPs were recovered through a simple sonochemical route and modified glassy carbon electrode was fabricated.…”
mentioning
confidence: 99%